The Notion of Quickness in Speech Dialectal Discourse - Sitkovskaya, Nadezhda (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
The aim of the research is study of ways of linguistic representation of one of culturally distinguished attributes of traditional folk culture – notion of quickness – in the material of Pskov regional study. The sources of information are narrative and folklore texts of different genres, which are preserved in Pskov archive of dialects, folklore and ethnography. One of the results of the research is the description of fairy tale texts, dealing with Shrovetide rite, and partly texts describing the ceremony of marriage (more than 300 units). The main method of research is component analysis of semantics of adjectival lexemes with general meaning “quick”. The work deals as well with the notion of dialectal discourse, which is considered to be the sum-total of speech realizations (separate utterances and complete texts of different volume and genre). The results of the research show that, despite the inhomogeneity of the archive text material, dialectal discourse preserves features of traditional system of values, including information on importance of quick response in different forms of rites.